The Potential of International Cooperation of Pohuwato Regency, Gorontalo Province: A Qualitative Explanatory Study - Ayuni Nur Siami; Sitti Nurtina (CV Edujavare Publishing, 2026)
Pohuwato Regency is located at the westernmost part of Gorontalo Province and possesses abundant natural resources, including metallic mineral mining, forestry, fisheries, agriculture, and biomass energy sectors. Amid fiscal constraints, international cooperation (paradiplomacy) has emerged as a strategic instrument to stimulate local economic growth. This study aims to analyze and explain the potential for international cooperation of Pohuwato Regency through a qualitative explanatory research method. Data were collected through document analysis, in-depth interviews with policymakers, and literature review from credible sources. The findings reveal that Pohuwato Regency has significant cooperation potential in four main areas: (1) biomass energy (wood pellet) exports to Japan and South Korea, already reaching USD 52 million annually, (2) gold and mineral mining cooperation with potential investor countries, (3) eco-tourism and marine tourism development, and (4) technical cooperation in agriculture and fisheries. The study concludes that strong institutional frameworks for international cooperation at the regency level are required, along with policy harmonization aligned with central government regulations (Permendagri No. 25/2020 and PP No. 28/2018), and a planned, sustainable regional economic diplomacy strategy